FORMATION, PROFESSIONAL IDENTITY, TEACHERS OF PHYSICAL EDUCATION AND DANCE: SOME NOTES (Fiep Bulletin - online, 2011)
This study aims to analyze the subject qualification, professional identity relating to dance and physical education issues. By means of literature researches the following considerations on the subject of the research are pointed out: regarding the identity of the professional of the Physical Education area who acts in the context of the dance, the research emphasizes the importance of having a strong background in scientific knowledge, without disregarding the practical experience in the area, since the teacher is not just a player in the reproduction of knowledge, but the subject of his own action. In this analysis we cannot ignore the identification process in which the dance professional is inserted and that the characteristics of his personal and professional background influence in the way this person becomes professional (teacher).
Keywords: professional identity; dance; physical education professional